1997
DOI: 10.1002/(sici)1096-8628(19970131)68:3<315::aid-ajmg13>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol and bile acid replacement therapy in children and adults with Smith-Lemli-Opitz (SLO/RSH) syndrome

Abstract: Tint et al. [N Engl J Med 1994, 330:107-113], working with blood samples from the Smith-Lemli-Opitz syndrome (SLOS) patients of Irons and Elias showed the biochemical basis of this disorder to be a cholesterol biosynthesis defect [Irons et al., Lancet, 1993, 341:1414]. Based on this finding, clinical protocols for cholesterol and bile acid replacement therapy were established in a few centers including the University of Pittsburgh. We report our experience with bile acid and/or cholesterol replacement therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
86
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 8 publications
1
86
0
Order By: Relevance
“…The most noted growth-related role of cholesterol is that it is a major component of cellular membranes. As might then be expected in persons unable to synthesize significant amounts of cholesterol, SLOS infants and children have diminished growth rates [6], which can be improved with dietary cholesterol [60][61][62]. It would be expected that fetal growth rates are also reduced.…”
Section: Discussionmentioning
confidence: 96%
“…The most noted growth-related role of cholesterol is that it is a major component of cellular membranes. As might then be expected in persons unable to synthesize significant amounts of cholesterol, SLOS infants and children have diminished growth rates [6], which can be improved with dietary cholesterol [60][61][62]. It would be expected that fetal growth rates are also reduced.…”
Section: Discussionmentioning
confidence: 96%
“…Treatment with simvastatin, an HMG-CoA reductase inhibitor, has been shown to decrease HMGCoA reductase activity and lower the production of 7-DHC in SLOS (28). Supplementation with dietary cholesterol is another option for potentially treating SLOS (29)(30)(31). We hypothesized that measurement of urinary mevalonate excretion in subjects with SLOS can be used to monitor HMG-CoA reductase activity in vivo to determine whether feedback inhibition of the enzyme occurs in SLOS and whether the rationale for using dietary cholesterol to inhibit synthesis of 7-DHC and its metabolites is sound.…”
mentioning
confidence: 99%
“…Increasing the amount of cholesterol available for efflux could have significant implications for the developing fetus. Recent studies have shown that increasing the amount of exogenous cholesterol available to the SLOS children after birth can have a positive impact on their development and well-being (17)(18)(19)(20). Therefore, increasing the supply of exogenous cholesterol as early as the embryonic or fetal stages may further improve the development, or lessen the severity, of possible birth defects in the SLOS fetus.…”
Section: Discussionmentioning
confidence: 99%
“…This defect results in abnormally low tissue and plasma cholesterol concentrations and causes a range of congenital birth defects from cranio-facial abnormalities to limb malformation to holoprosencephaly (13,16). Cholesterol supplementation in children with SLOS has resulted in vast clinical improvement, including enhanced growth, rapid developmental progress, and lessening of behavioral problems (17)(18)(19)(20). Due to these marked improvements postpartum, exogenous cholesterol may also enhance the development of the fetus and possibly lessen the severity of birth defects.…”
mentioning
confidence: 99%